Interspecific hybridization in Cucumis leads to the divergence of phenotypes in response to low light and extended photoperiods - Yu, Xiaqing; Hyldgaard, Benita; Rosenqvist, Eva; Ottosen, Carl-Otto; Chen, Jinfeng (Frontiers in Plant Science, 2015)
With the aim of improving shade tolerance of cucumber, Cucumis ×hytivus, a newly synthesized allotetraploid, was obtained by crossing a shade tolerant wild relative, C. hystrix, with a cultivated cucumber, C. sativus L. ‘BejingJietou’. The results show that the new C. ×hytivus only partly is an intermediate hybrid and it has not only chlorophyll deficiency, which recovers during leaf development, but also lower carotenoid content. Three light conditions with the combination of different light intensities and photoperiods were employed to investigate the photosynthetic response of these three Cucumis species to low light and long photoperiod. The consistent order of Pmax and DWS being lowest in C. hystrix, medium in C. ×hytivus and highest in ‘BejingJietou’ suggests the three species to have genetically different photosynthetic efficiency, which relates well with the natural habitats of the parent species and the hybrid as intermediate. C. ×hytivus appears to be inhibited by the low light levels to the same extent as the cultivated ‘BeijingJietou’, which indicates neither improvement of shade tolerance nor hypothetical heterosis effect in C. ×hytivus. However, unexpectedly, the PSII of C. hystrix was affected by the long photoperiod in the long term, suggested by the decrease of Fv/Fm. This sensitivity towards day length has not been passed on to C. ×hytivus.